2015
DOI: 10.1089/bio.2014.0054
|View full text |Cite
|
Sign up to set email alerts
|

Method Validation for Automated Isolation of Viable Peripheral Blood Mononuclear Cells

Abstract: We validated the first fully automated method for isolating viable PBMCs, including RNA analysis and generation of LCLs. We recommend processing within 8 h of blood collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…A, B: freshly isolated PBMC (n = 6). C, D: cryopreserved PBMC (n = 3) Isolation by cell separation tubes requires less skill than isolation with Ficoll gradient, and is compatible with automation [40]. CPT, Accuspin, and Ficoll isolation methods have shown similar performance on PBMC recovery and viability [17].…”
Section: Pbmc Isolationmentioning
confidence: 99%
“…A, B: freshly isolated PBMC (n = 6). C, D: cryopreserved PBMC (n = 3) Isolation by cell separation tubes requires less skill than isolation with Ficoll gradient, and is compatible with automation [40]. CPT, Accuspin, and Ficoll isolation methods have shown similar performance on PBMC recovery and viability [17].…”
Section: Pbmc Isolationmentioning
confidence: 99%
“…Nucleic acids with little or no PCR or RT-qPCR product indicate tissue degradation and poor quality 6 . Our results showed acceptable Ct values, which is a good indicator of the suitability of the material for subsequent use in biomedical research 35 .…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, it has been shown that time from venipuncture to PBMC isolation and cryopreservation may affect the cell quantity, recovery, viability, white blood cells subpopulation distribution, gene expression, and lymphoblastoid cell lines transformation 35 and also have impact in the viability and performance of T cells in downstream immunological assays [36][37] and in the cytotoxic activity of natural killer cells 38 . In addition, it has also been shown that a 24-h delay between blood collection and processing, especially at 4ºC, significantly increases granulocyte contamination, which may inhibit T cell function 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential solution is to integrate automation to the sample processing workflow. Instruments such as liquid handlers offer protocols for automated processing which have been shown to perform as efficiently as the goldstandard Ficoll density gradient method, as measured by overall yield, viability, recovery, white blood cell subpopulation distribution, and gene expression (16)(17)(18)(19).…”
Section: Sample Preparation and Storage: The Crucial First Stepmentioning
confidence: 99%